2012
DOI: 10.3109/14015439.2012.664653
|View full text |Cite
|
Sign up to set email alerts
|

Testing the phonemes relevant for German verb morphology in hard-of-hearing children: The FinKon-test

Abstract: Many hard-of-hearing children show delays or disorders in the acquisition of morphology and syntax. There is an on-going discussion how these difficulties are connected to problems in the auditory domain. The article focuses on coronal consonants that function as suffixes in the German verbal inflectional system. Here we present a new test we developed to evaluate the ability to discriminate these consonants in syllabic offset positions. A pilot study with 22 hearing-impaired (HI) children and 15 typically dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It has been shown by Hennies et al (2012), that German-speaking HI children perform worse than normal-hearing children on the perception of consonants that are relevant for subject-verb agreement on syllable offset. Furthermore, Szagun (2004) showed that the article system of German-speaking children with a CI (cochlear implant) is less well-developed than that in normal hearing children, which she argues is the result of persisting perceptual problems.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown by Hennies et al (2012), that German-speaking HI children perform worse than normal-hearing children on the perception of consonants that are relevant for subject-verb agreement on syllable offset. Furthermore, Szagun (2004) showed that the article system of German-speaking children with a CI (cochlear implant) is less well-developed than that in normal hearing children, which she argues is the result of persisting perceptual problems.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that children with CIs perceive morphosyntactic cues less well than children with NH, because these cues are perceptually not very salient. Case forms such as der "the NOM " and den "the ACC " or welcher "which NOM " and welchen "which ACC " have been argued to be difficult to discriminate perceptually; the same holds for agreement morphology with respect to number (e.g., the third-person singular -s morpheme) on the verb (Hennies, Penke, Rothweiler, Wimmer, & Hess, 2012).…”
Section: Perception Of Morphosyntactic Cuesmentioning
confidence: 99%